PERKEMBANGAN YAYASAN PERGURUAN WAHIDIN DI KOTA BAGANSIAPIAPI PADA TAHUN 1987-2014 - Sari, Novita; Ibrahim, Bedriati; Asril, Asril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This thesis is entitled "The Development of Wahidin Education Foundation in Bagansiapiapi City in 1987-2014". The purpose of this research is to find out (1) how the history of the establishment of the Wahidin Education Foundation (2) How the development of the Wahidin College Foundation in 1987-2014 (3) The role of Chinese ethnicity in the Wahidin College Foundation. This research uses a historical approach, data collection methods with field studies in the form of observations and interviews as well as archival and document studies. This research was conducted at the Wahidin Education Foundation School in the City of Bagansiapiapi. After the data has been collected, data testing is carried out with source criticism, namely by testing the authenticity of the sources and comparing one data to another, such as comparing the results of interviews with written evidence. Based on the results of this study it was concluded that the Wahidin Education Foundation School was born with a background of several ethnic Chinese in Bagansiapiapi, in 1957 at which time the educational conditions in the city of Bagansiapiapi lacked fields for schools. So some of the ethnic Chinese and the surrounding community agreed to build the Wahidin Education Foundation, considering the importance of education. The founder of the Wahidin Education Foundation also hopes that this school can form a young generation who has competence, a sense of nationalism and a strong foundation of religious education according to their respective beliefs. The research results of this thesis are: (1) The Wahidin School of Education Foundation was founded in 1957, the first initiator was Kapitan Weng and was legally legalized in 1967 in front of a notary. (2) The Wahidin College Foundation School has experienced quite rapid development over the years, in several aspects such as the number of students, the number of teachers and several equipment that meet educational needs. (3) The role of Chinese ethnicity plays a very important role in the development of their special education in the city of Bagansiapiapi as evidenced by the establishment of the Wahidin Education Foundation.Key Words: Wahidin Educational Foundation in Bagansiapiapi City